KPPU Assembly's Ruling on Law Number 5 of 1999 Addresses Monopolistic Practices and Unfair Competition - Fazaroh, Hilma Irodatul; Widiyanti, Ikarini Dani; Kusuma, Ajeng Pramesthy Hardiani (Kertha Patrika; Vol 46 No 3 (2024)DO - 10.24843/KP.2024.v46.i03.p.02, 2024)
KPPU Decision Case Number 13/KPPU-M/2022, according to KPPU there was a delay in notification of the takeover of PT shares. Bakti Gemilang Anak Sejahtera by PT. Indonesian House of Love. This research aims to examine the suitability of the KPPU panel decision Number 13/KPPU-M/2022 with the provisions of Law Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition. The research method in this research is a normative juridical method, where the research focuses on reviewing the decision of the Business Competition Supervisory Commission (KPPU) Number 13/KPPU-M/2022 and several related statutory regulations. on statutory regulations. Through this research it can be concluded that KPPU Decision Number 13/KPPU-M/2022 concerning PT. Rumah Kasih Indonesia which acquired the shares of PT. Bakti Gemilang Anak Sejahtera is required to notify the KPPU of share takeovers. PT. Rumah Kasih Indonesia made an acquisition resulting in excess asset value and sales value. Decision Number 13/KPPU-M/2022 legally violates the provisions of Article 29 of Law no. 5 of 1999 so that a sanction of 1 billion rupiah is imposed.